FEATURES OF PROFESSIONAL THINKING AS A RESOURCE FOR OVERCOMING EMOTIONAL INSTABILITY IN THE TEACHING PROFESSION (Psychology Travelogs, 2023)
The article is devoted to the analysis of the relationship and features of professional thinking and emotional instability in teachers. The demands of practical social and psychological support of representatives of "person-to-person" professions in the period of military-political and socio-economic instability have led to the consideration of emotional instability from the standpoint of the relationship with professional thinking, which is able to introduce new professional and personal meanings into the process of activity, thereby becoming a cognitive resource. It is shown that supra-situational thinking negatively correlates with emotional instability, and situational thinking – positively. It is noted that emotional instability is more pronounced in doctors. It has been found that the adequacy and sufficiency of the analysis of a problem situation are positively related to self-assessment of professional success and self-satisfaction, and the validity – to the ability to cope with the experience of psychotraumatic circumstances. The high efficiency of the analysis decreases emotional involvement in work, and the increase in the depth of the analysis increases emotional burnout. The obtained results on the partial relationship between the components of professional thinking and indicators of emotional instability can be used as arguments for the author's position on the possibility of effective use of thinking as a cognitive resource for solving actual practical problems. It is shown that the resourcefulness of professional thinking can be considered as an indicator that prevents the manifestations of emotional instability, which makes it possible to outline the resource functions of professional thinking, which are manifested in further cognitive and reflective events. In-depth analysis of the situation and argumentation of the used methods of action are associated with a reduced emotional background during the experience of psychotraumatic situations.
Keywords: professional thinking; emotional instability; teachers; emotional involvement; cognitive resource